2020
DOI: 10.3389/fphar.2020.600561
|View full text |Cite
|
Sign up to set email alerts
|

Exploration the Mechanism of Doxorubicin-Induced Heart Failure in Rats by Integration of Proteomics and Metabolomics Data

Abstract: Heart failure is a common systemic disease with high morbidity and mortality worldwide. Doxorubicin (DOX) is a commonly used anthracycline broad-spectrum antitumor antibiotic with strong antitumor effect and definite curative effect. However, cardiotoxicity is the adverse reaction of drug dose cumulative toxicity, but the mechanism is still unclear. In this study, proteomics and metabonomics techniques were used to analyze the tissue and plasma of DOX-induced heart failure (HF) in rats and to clarify the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Protein identifications were performed using the MASCOT search engine (version 2.3.2; Matrix Science, London, UK) embedded into Proteome Discoverer 1.4 (Thermo Electron, San Jose, CA, USA) [ 15 ] (Suplementary information). The LC/MS raw data were searched in the UniProt-reviewed rat protein database and differentially expressed proteins were screened by the criteria of up-regulation greater than 1.2 times or down-regulation less than 0.833 and T-test P value less than 0.05 [ 3 ]. The statistical analysis of related data was performed using SPSS software 20.0.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein identifications were performed using the MASCOT search engine (version 2.3.2; Matrix Science, London, UK) embedded into Proteome Discoverer 1.4 (Thermo Electron, San Jose, CA, USA) [ 15 ] (Suplementary information). The LC/MS raw data were searched in the UniProt-reviewed rat protein database and differentially expressed proteins were screened by the criteria of up-regulation greater than 1.2 times or down-regulation less than 0.833 and T-test P value less than 0.05 [ 3 ]. The statistical analysis of related data was performed using SPSS software 20.0.…”
Section: Methodsmentioning
confidence: 99%
“…Although the roles of the two main causes in MetS are plausible, its specific pathogenesis still remains unknown and it also lacks screening and optimal treatment for this disease. Currently, proteomics and metabonomics have been promising technologies for elucidating the mechanisms of diseases, which detect and identify various molecules at the levels of proteins and metabolites, and study their functions and interrelationships among various molecules [ 3 , 4 ]. Yu Yuan et al combined the two techniques to explore the mechanism of doxorubicin-induced heart failure in rats and found that PTP1B can be used as a potential target for the treatment of heart failure [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In metabolomic studies conducted on rats, disorders with energy metabolism, fatty acids oxidation, amino acids, purine and choline metabolism, and gut microbiota-related metabolism were all associated with DOX administration [50]. Treated rats display a reduction in crucial mitochondrial elements, including superoxide dismutase (SOD) and nuclear respiratory factor 2 (NRF-2), which mediate stress response, and protein tyrosine phosphatase 1B (PTP1B), whose activation impairs insulin receptor substrate 1 (IRS-1), leading to disorders of fatty acid metabolism and glycolysis [51]. Aldose reductase promotes high glucose-induced superoxide overproduction insult.…”
Section: Metabolic Derangementsmentioning
confidence: 99%
“…Doxorubicin has been hypothesised to directly affect cardiac substrate usage. In particular, radiotracer and metabolomics studies in rats have suggested a decrease in both glucose and fatty acid utilisation preceding the onset of cardiac functional decline [ 26 , 27 ]. Some rat studies have suggested doxorubicin inhibits fatty acid oxidation by preventing mitochondrial entry of long-chain fatty acids through direct inhibition of carnitine palmitoyltransferase I (CPT I) [ 28 ], whilst others have suggested this to be due to transcriptional alterations in the fatty acid oxidation pathway within mitochondria [ 29 ].…”
Section: Metabolic Dysfunction Leading To Cardiotoxicity Of Specific Chemotherapiesmentioning
confidence: 99%